Multiple sclerosis susceptibility and the X chromosome - Herrera, BM; Cader, MZ; Dyment, DA; Bell, JT; DeLuca, GC; Willer, CJ; Lincoln, MR; Ramagopalan, SV; Chao, M.; Orton, S-M.; Sadovnick, AD; Ebers, GC (Multiple sclerosis, 2007)
Multiple sclerosis (MS) is a chronic autoimmune complex trait with strong evidence for a genetic component. A female gender bias is clear but unexplained and a maternal parent-of-origin effect has been described. X-linked transmission of susceptibility has been previously proposed, based on pedigree, association and linkage studies. We genotyped 726 relative pairs including 552 affected sib-pairs for 22 X-chromosome microsatellite markers and a novel dataset of 195 aunt-uncle/niece-nephew (AUNN) affected pairs for 18 markers. Parent-of-origin effects were explored by dividing AUNN families into likely maternal and paternal trait transmission. For the sib-pair dataset we were able to establish exclusion at a λ s = 1.9 for all markers using an exclusion threshold of LOD ≤—2. Similarly for the AUNN dataset, we established exclusion at λAV = 1.9. For the combined dataset we estimate exclusion of λ = 1.6. We did not identify significant linkage in either the sib-pairs or the AUNN dataset nor when datasets were stratified for the presence/absence of the HLA-DRB1*15 allele or for paternal or maternal transmission. This comprehensive scrutiny of the X-chromosome suggests that it is unlikely to harbour an independent susceptibility locus or one which interacts with the HLA. Complex interactions including epigenetic ones, and masking by balanced polymorphisms are mechanisms not excluded by the approach taken. Multiple Sclerosis 2007; 13 : 856—864. http://msj.sagepub.com